Mental health morbidities in Kerala, India: Insights from National Mental Health Survey, 2015–2016 - Sonakshi Jyrwa; T. M. Shibukumar; Jayakrishnan Thavody; P. K. Anish; Thomas Bina; K.R. Rajith; Pradeep S. Banandur; Girish N. Rao; Gopalkrishna Gururaj; Mathew Varghese; Vivek Benegal (Indian Journal of Psychiatry)
Background: The National Mental Health Survey was borne out of the felt need for a comprehensive epidemiological survey on mental health to understand the magnitude of psychiatric morbidities in India to aid in mental health policymaking, service planning, and delivery. Kerala was one of the 12 surveyed states, representing southern India. Aims: To estimate the prevalence and pattern of various mental illnesses and substance use disorders in a representative sample from Kerala state. Settings and Design: A household survey using a multi-stage, stratified, random cluster sampling technique, with selection based on probability proportionate to size at each stage. Materials and Methods: The community-based survey was carried out by trained field staff on individuals from systematically selected households from three randomly selected districts of Kerala. The instruments used in the survey included M.I.N.I adult version 6.0, a modified version of the Fagerström Nicotine Dependence Scale and questionnaires to screen for epilepsy, intellectual disability, and autism spectrum disorders. Results: A total of 2479 respondents aged >18 years were interviewed. The lifetime and current prevalence of mental morbidity (excluding tobacco use disorders) was 14.14% and 11.36%, respectively. Neurotic/stress-related disorders and depressive disorders were 5.43% and 2.49%, respectively, while severe mental disorders were prevalent in 0.44% of the sample. The prevalence of high risk for suicide was 2.23%. Conclusions: The survey revealed high rates of common mental illnesses and suicide risk in the state when compared to national estimates.